Upaya Meningkatkan Hasil Belajar Ekonomi dengan Menggunakan Media Kongkrit pada Peserta Didik Kelas XI SMK YPSEI Palangka Raya Tahun Pelajaran 2014/2015 - Yeni Yeni; Santi Endriani (Neraca: Jurnal Pendidikan Ekonomi, 2019)
This study aims to: (1) To improve learning activities by using concrete media on economic subjects, (2) To improve the learning outcomes of Economics by using concrete media on students of class XI YPSEI Vocational School in Palangka Raya. The method used by researchers is to use a class action research design (CAR) that seeks to solve or answer the problems faced in the current situation. For data collection techniques used are tests and observations. While in this study using the percentage of classical and individual completeness formula. The results of the study show that: (1) Learning activities of students using concrete media money in learning is more active and applied. In the first cycle the score of learning activities was 3.4 with good categories, then in the second cycle 3.73 with good criteria, (2) There was an increase in student learning outcomes in economic lessons using concrete money media. The pre-action average value of 35.25 and completeness in classical 5%. The average value in cycle I 51.25 and completeness in classical 45%. The average value in cycle II 88 is 100% classical.